2017
DOI: 10.1177/1464420717719474
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of ultrasonic and conventional shot peening: A comparison of the effect of both processes on surface conditions

Abstract: This paper presents three-dimensional-dynamic finite element simulations of both conventional and ultrasonic peening processes. The proposed models have the advantages of being very close to reality and of taking into account the majority of the influencing factors linked to the processing parameters, the shot–target contact conditions and the monotonic-cyclic elastic–plastic behavior law coupled to the damage of the treated material. The implementations of these simulations allow predicting the changes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The mass flow rate kg=m 2 s À Á of the particles is a time-varying parameter that depends on the ability of the DEM-based generator to insert particle of a specified size. It is formulated as the function of the mass (kg) flowing through the nozzle inlet per unit area A m 2 ð Þ and time (s). The shots flow speed is used to specify the speed at which the generated particles are impacted on the target.…”
Section: Modelling Of the Sp Process Using Coupled Fem-demmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass flow rate kg=m 2 s À Á of the particles is a time-varying parameter that depends on the ability of the DEM-based generator to insert particle of a specified size. It is formulated as the function of the mass (kg) flowing through the nozzle inlet per unit area A m 2 ð Þ and time (s). The shots flow speed is used to specify the speed at which the generated particles are impacted on the target.…”
Section: Modelling Of the Sp Process Using Coupled Fem-demmentioning
confidence: 99%
“…Shot peening (SP) is a mechanical cold working process for enhancing the fatigue strength of materials (alloys and metals) by inducing superficial compressive residual stress (CRS). [1][2][3] The process is a bit complex as it involves striking a surface with thousands of spherical media (shots) at a high velocity sufficient enough to cause plastic deformation. Indents are formed all over the peened region as the shots hit the target, which stretches the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that USP induces highly random and repetitive impacts within a specific tooling chamber, resulting in improved surface quality and a deeper compressive residual stress layer [10][11][12]. Furthermore, research has suggested that increasing the intensity of USP elevates the average roughness but decreases the dispersion of roughness distribution [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…25 Manchoul et al proposed three-dimensional dynamic finite element simulations of conventional peening processes, and the results showed that the developed models have been used to predict the effect of shot velocity, shot size, and the number of impacts on the induced RS profiles, and this study illustrates that both the number of impacts and the shot velocity affect the magnitude of the maximum CRS. 26 Although many valuable results of AWJP are achieved in the above-mentioned literatures, however, AWJSP after multiple passes and under full coverage condition is still not achieved. Besides, the above literatures mainly focus on the magnitude and depth of CRS, and little attention has been paid to study the formation mechanism of the surface topography, the coupling mechanism of RS, and distribution uniformity of RS after multiple passes AWJSP.…”
Section: Introductionmentioning
confidence: 99%